The effects of short-term fish oil supplementation on pulmonary function and airway inflammation following a high-fat meal. - Harms, Craig A.; Rosenkranz, Sara K.; Ade, C. J. (My University, 2014)
Introduction Many environmental and dietary influences can cause immune cells to produce biological mediators that increase airway inflammation. A high-fat meal (HFM) is one stimulus that increases airway inflammation in healthy individuals. Supplementation with omega-3 fatty acids can reduce inflammation systemically and may be beneficial to the airways. Purpose To determine if omega-3 fatty acid supplementation via fish oil would mitigate the airway inflammatory response induced by a single HFM. Methods Seventeen non-asthmatic men (22 ± 2 years.) were supplemented with 3,000 mg × day⁻¹ fish oil or a placebo for 3 weeks. Fractional exhaled nitric oxide (FENO; a marker of airway inflammation), impulse oscillometry (a measure of respiratory impedance), pulmonary function, and triglycerides were measured prior to and 2 h following a HFM. Results Following a HFM, triglycerides increased in both fish oil and placebo groups compared to pre-HFM (~59 and ~49 %, respectively, p < 0.05). The percent increase in FENO was greater in the placebo group compared to the fish oil group (25.7 ± 16.7 vs. −1.99 ± 10.5 %, respectively, p < 0.05). A significant correlation was observed between blood triglycerides and FENO in the placebo group (r = 0.61; p < 0.05), but not the fish oil group (p = 0.21). Conclusion A single HFM increases airway inflammation and omega-3 fatty acid supplementation via fish oil protects against HFM associated changes in airway health.
Keywords: Airway inflammation; High-fat; Fish oil; Pulmonary function